The synthesis of 2-pyrimidinone nucleosides and their incorporation into oligodeoxynucleotides. - Gildea, B (1989)
The synthesis of 1-(beta-D-2'-deoxyribosyl)-2-pyrimidinone (dK) and its 5-methyl derivative (d5) from 2'-deoxycytidine or 2'-deoxythymidine, respectively, via silver oxide oxidation of 4-hydrazinopyrimidines is described. The necessary hydrazine substituted pyrimidine nucleosides have been prepared by transamination of a protected cytidine derivative or by addition/elimination reactions to an O4-sulfonated thymidine derivative. Oxidation of the 4-hydrazino pyrimidines was complicated by a competing hydrolytic reaction which generated 2'-deoxyuridine or 2'-deoxythymidine. However, in the presence of an organic base such as triethylamine, oxidation became the predominant reaction. After suitable protection and formation of the 3'-phosphoramidite derivatives, these modified nucleosides were incorporated into seven self-complementary oligodeoxynucleotides by chemical synthesis using phosphite triester methodology. Oligodeoxynucleotides were prepared such that dA-dT and dG-dC base pairs were substituted by dA-d5 or dG-dK base pairs, respectively. Both circular dichroism spectra and thermal denaturation studies were used to characterize the modified oligodeoxynucleotides.